Ответы и объяснения

Лучший Ответ!
  • Yena
  • главный мозг
2013-05-22T18:04:35+00:00

(\frac{2}{a^{\frac{2}{3}}-4}}+\frac{2}{2-a^{\frac{1}{3}}}-\frac{1}{2+a^{\frac{1}{3}}}): ( \frac{4-a^{\frac{2}{3}}}{3})^{-1}=\\\ \\\ =(\frac{2}{(a^{\frac{1}{3}}-2)(a^{\frac{1}{3}}+2)}}-\frac{2}{a^{\frac{1}{3}}-2}}-\frac{1}{2+a^{\frac{1}{3}}})* \frac{(a^{\frac{1}{3}}-2)(a^{\frac{1}{3}}+2)}{3}=\\\ \\\ =\frac{2-2(a^{\frac{1}{3}}+2)-(a^{\frac{1}{3}}-2)}{(a^{\frac{1}{3}}-2)(a^{\frac{1}{3}}+2)}}* \frac{(a^{\frac{1}{3}}-2)(a^{\frac{1}{3}}+2)}{3}=\\\

=\frac{2-2a^{\frac{1}{3}}-4-a^{\frac{1}{3}}-2}{3}=\frac{-3a^{\frac{1}{3}}-4}{3}} =-\frac{3a^{\frac{1}{3}}+4}{3}}

 

 

....................................................................................................................